Curcuma decreases serum hepcidin levels in healthy volunteers: a placebo‐controlled, randomized, double‐blind, cross‐over study. (7th May 2017) - Lainé, Fabrice; Laviolle, Bruno; Bardou‐Jacquet, Edouard; Fatih, Nadia; Jezequel, Caroline; Collet, Nicolas; Ropert, Martine; Morcet, Jeff; Hamon, Catherine; Reymann, Jean‐Michel; Loréal, Olivier
Abstract: Hepcidin, secreted by hepatocytes, controls iron metabolism by limiting iron egress in plasma. Hepcidin is upregulated during inflammation through the activation of the signal transducer and activator of transcription 3 (STAT3) transduction pathway, which decreases iron bioavailability and may explain the anemia of chronic inflammatory disease. In vitro, it has been shown that curcumin can decrease hepcidin synthesis by decreasing STAT3 activity. We conducted a proof‐of‐concept study to assess the effect of curcuma on hepcidin synthesis in human. This was a placebo‐controlled, randomized, double‐blind, cross‐over, two‐period study performed in 18 healthy male volunteers. Subjects received a single oral dose of 6 g curcuma containing 2% of curcumin or placebo. Serum hepcidin and iron parameters were assessed repeatedly until 48 h after dosing. When compared with a placebo curcuma decreased hepcidin levels significantly at 6 h (−19%, P = 0.004), 8 h (−17%, P = 0.009), and 12 h (−17%, P = 0.007) and tended to decrease hepcidin at 24 h (−15%, P = 0.076). Curcuma also significantly increased serum ferritin levels at 6 and 8 h (+7% for both times, P = 0.018, 0.030, respectively) and had no effects on serum iron, transferrin, and transferrin saturation. This pilot study showed that curcuma decreases serum hepcidin levels in human and supports the idea that curcuma could be useful in treating hepcidin overproduction during inflammatory processes. Confirmatory studies in patients with chronic inflammation are now required to determine the optimal dose and therapeutic scheme of curcuma.